CRISPR/Cas Genome Editing and Precision Plant Breeding in Agriculture - Chen, Kunling; Wang, Yanpeng; Zhang, Rui; Zhang, Huawei; Gao, Caixia (Annual review of plant biology, 2019)
Enhanced agricultural production through innovative breeding technology is urgently needed to increase access to nutritious foods worldwide. Recent advances in CRISPR/Cas genome editing enable efficient targeted modification in most crops, thus promising to accelerate crop improvement. Here, we review advances in CRISPR/Cas9 and its variants and examine their applications in plant genome editing and related manipulations. We highlight base-editing tools that enable targeted nucleotide substitutions and describe the various delivery systems, particularly DNA-free methods, that have linked genome editing with crop breeding. We summarize the applications of genome editing for trait improvement, development of techniques for fine-tuning gene regulation, strategies for breeding virus resistance, and the use of high-throughput mutant libraries. We outline future perspectives for genome editing in plant synthetic biology and domestication, advances in delivery systems, editing specificity, homology-directed repair, and gene drives. Finally, we discuss the challenges and opportunities for precision plant breeding and its bright future in agriculture.